Preparation and in-Vitro Evaluation of Mucoadhesive Clotrimazole Vaginal Hydrogel - I. Abdul, Basma; A. Rajab, Nawal (Iraqi Journal of Pharmaceutical Sciences, 2017)
Clotrimazole (CLO) is an antimycotic imidazole derivative applied locally for the treatment of vaginal yeast infections. In this study, CLO was formulated as vaginal mucoadhesive hydrogel, using different types of mucoadhesive polymers to ensure prolonged contact between active ingredient and vaginal mucosa. Physicochemical properties of the prepared formulas were evaluated as a visual inspection, pH, swelling index, spreadability, and mucoadhesive characteristics, in addition to an in-vitro drug release. The influence of type and concentration of polymers as CMC-Na (1.5, 2.5, and 3.5%w/w), carbopol 940( 0.25, 0.5, and 1 %w/w) and poloxamer 407 (15, 25, 30%w/w) on CLO release from the prepared gels were also investigated. All the different concentrations of each polymer gave a percent of drug release profile inversely proportional with the polymer concentration. The lowest concentration showed faster release within the first half an hour of 99Â± 2% of drug release , while CMC-Na at 3.5% (F2) demonstrated the least release of 40 % after three hours. On the other hand, poloxamer 407 of 25% gel (F7) produced the highest release of 98%, while carbopol 1% (F5) and CMC-Na (F1) produced 85% and 80% ,respectively. All the prepared formulas were following Higuchi kinetic model. Based on overall result, CLO can be formulated as mucoadhesive vaginal hydrogel using 25%poloxamer as the best prepared formula. Key words: Hydrogel, Clotrimazole, Mucoadhesive